Effects of Urbanization on Water Quality and the Macrobenthos Community Structure in the Fenhe River, Shanxi Province, China - Linfang Wang; Hua Li; Jinhua Dang; Ying Zhao; Yu’en Zhu; Pengming Qiao (Journal of Chemistry)
The relationships between land use types, water and sediment parameters, and macrobenthos community structures in the upper and middle reaches of the Fenhe River and urbanization intensity were studied. Samples were collected from 23 sampling sites. Spearman rank correlation analyses were performed to assess the relationships between the percentages of impervious area or the proportions of four land uses and the water and sediment physicochemical properties, heavy metal and polycyclic aromatic hydrocarbon concentrations in water and sediment, and biological indicators of the macrobenthos communities. Some water parameters (temperature, oxidation-reduction potential, electrical conductivity, total N concentration, total P concentration, ammonia-N concentration, and nitrate-N concentration), some sediment parameters (total N concentration, total P concentration, organic matter content, percentage of particles with diameters <2 mm, and polycyclic aromatic hydrocarbon, Cd, Cr, Cu, Ni Pb, and Zn concentrations), and some macrobenthos parameters (Berger–Parker index and percentages of collectors, tolerant taxa, and Oligochaeta) significantly positively correlated with the percentage of impervious area. Some water parameters (pH and dissolved oxygen concentration), some sediment parameters (percentage of particles with diameters >2 mm), and some macrobenthos parameters (total biomass, total number of taxa, Shannon’s index, N diversity index, and percentages of Ephemeroptera, Plecoptera, Trichoptera, filterers, scrapers, and sensitive taxa) significantly negatively correlated with the percentage of impervious area. The results indicate that intensification of urbanization has strongly affected the water, sediment, and macrobenthos in the Fenhe River watershed.